Physical and molecular identification of fish and shrimp diseases in some farms of West Java, Banten and Jakarta, Indonesia - Adam Saba Anggara; Ida Ayu Mirah Meliana Dewi; Kismono Kudoasmoro; Putu Eka Sudaryatma; Putu Angga Wiradana (Jurnal Akuakultur Indonesia, 2024)
Infectious disease is a major challenge in fish and shrimp farming systems caused by microorganisms including bacteria, viruses and parasites. Physical detection has limitations in detecting diseases in cultivated animals earlier, because of the varied clinical symptoms. The aims of this study was to identify the physical and molecular presence of infectious pathogens in fish and shrimp cultivated in several ponds in West Java, Banten and Jakarta. Monitoring was carried out in two stages, namely the period March–April 2021 and September 2021 by taking samples from several ponds in Bogor, Tangerang, Depok and Jakarta. The sample criteria used were fish and shrimp showing normal and clinical symptoms of being attacked by a disease which were collected by purposive sampling. The collected samples were examined in two stages, namely physical examination of clinical symptoms and molecular examination using PCR. The results showed that of the 24 species samples collected, 17 species showed normal clinical symptoms and seven species showed clinical symptoms. Of the 24 fish and shrimp samples, four samples were infected (2 samples from normal species and 2 samples with clinical symptoms). The infected normal samples were Osphronemus goramy and Litopenaeus vannamei. The infected samples with clinical symptoms were Carassius auratus by Aeromonas salmonicida and red zebra cichlid (Metriaclima estherae) by Red Sea Bream Iridoviral Disease (RSBIV). Physical testing supported by molecular detection of aquatic animals can be an effort to manage aquaculture systems in Indonesia. Keyword: aquaculture, emerging disease, fisheries products, molecular assay ABSTRAK Penyakit infeksi adalah tantangan utama pada sistem budidaya ikan dan udang yang disebabkan oleh mikroorganisme termasuk bakteri, virus, dan parasit. Deteksi secara fisik memiliki keterbatasan dalam mengetahui lebih dini penyakit pada hewan budidaya, karena gejala klinis yang bervariasi. Tujuan dari penelitian ini adalah untuk melakukan identifikasi fisik dan molekuler keberadaan patogen infeksi pada ikan dan udang yang dibudidayakan di beberapa pertambakan di Jawa Barat, Banten, dan Jakarta. Pemantauan dilakukan dalam dua tahap yaitu periode Maret – April 2021 dan September 2021 dengan mengambil sampel dari beberapa pertambakan di Bogor, Tangerang, Depok, dan Jakarta. Kriteria sampel yang digunakan adalah ikan dan udang yang menunjukkan gejala klinis terserang oleh penyakit yang dikumpulkan secara purposive sampling. Sampel yang terkumpul diperiksa dalam dua tahap yaitu pemeriksaan fisik gejala klinis dan pemeriksaan molekuler menggunakan PCR. Hasil menunjukkan dari 24 sampel spesies yang terkumpul, sebanyak 17 spesies menunjukkan gejala klinis normal dan tujuh spesies menunjukkan gejala klinis. Dari 24 sampel ikan dan udang, terdapat empat sampel yang terinfeksi (2 sampel dari spesies normal dan 2 sampel dengan gejala klinis). Sampel normal yang terinfeksi adalah Osphronemus goramy dan Litopenaeus vannamei. Sampel yang terinfeksi dengan gejala klinis adalah Carassius auratus oleh Aeromonas salmonicida dan red zebra cichlid (Metriaclima estherae) oleh Red Sea Bream Iridoviral Disease (RSBIV). Pengujian fisik yang didukung dengan deteksi molekuler pada hewan budidaya dapat menjadi upaya manajemen sistem akuakultur di Indonesia. Kata kunci: akuakultur, emerging disease, perikanan, pengujian molekuler